Analisis Faktor-faktor Yang Berpengaruh Terhadap Pengentasan Kemiskinan Di Bali: Analisis FEM Data Panel - Sri Budhi, Made Kembar (Jurnal Ekonomi Kuantitatif Terapan; 2013: Vol. 6, No. 1, Februari 2013 (pp. 1-70), 2013)
Poverty is a macroeconomic pathology that faced by all countries in the world including Indonesia. Bali as a part of Indonesia will also face the same problem. Based on BPS data in 2010, Bali has 174.900 people who life in poor condition, which is 4,88 percent of all residence. High economic growth (GDRP growth) that have achieved cannot significantly reduce number of poor people. This study analyzed the impact of education program, number of population, GDRP, share of agricultural sector, and share of industry sector toward poverty in Bali. The analysis using panel data of nine city/districts from 2006 to 2009, and estimated using Fixed Effect Model. The results show that the percentages of poor people who graduate from the nine-year education program not significantly reduce poverty. Number of population, GDRP, and share of agricultural sector has positive and significant effect toward poverty; meanwhile share of industry sector has negative and significant effect toward poverty.
Keywords: poor people; economic growth; nine-year education program; FEM panel data